Carbon Emission Disclosure: Kinerja Lingkungan, Carbon Performance Dan Board Diversity - Sadira Ashia Priliana; Husnah Nur Laela Ermaya (Universitas Serang Raya, 2023)
This study aims to see the effect of environmental performance, carbon performance and board diversiy on carbon emission disclosure. The population used in this study are non-financial companies listed on the Indonesia Stock Exchange in 2018-2020. The sample obtained in this study was conducted using purposive sampling method by producing 92 samples of companies. Hypothesis testing was carried out using multiple linear regression analysis. Based on the results of the multiple regression test and the t-test, the results show that environmental performance has an effect on carbon emission disclosures, while the variable carbon performance, foreign diversity and company size have no effect on carbon emission disclosures. Keywords: Carbon Emission Disclosure, Environmental Performance, Carbon Performance, Board Diversity, Company Size.